A bibliometric and subject analysis of 3300 most‐cited articles in dentistry. Issue 5 (7th August 2022) - Daryakenari, Ghazaleh; Batooli, Zahra
Abstract: Objectives: This study aims to analyze the publications that have studied top‐cited articles in dentistry. Material and Methods: The study is applied research in terms of the purpose and scientometrics descriptive in terms of type, which has been done using the Retrospective Bibliometric Analysis. To retrieve the 100 most‐cited studies in Scopus, an advance search was used. The search results indicate that 33 articles focused on analyzing the 100 most‐cited publications on oral and dental subjects. The bibliographic information, including author, journal, country, institution, citation count, and citation density was analyzed. Then the full text of the articles was reviewed to identify the most productive journal, country, and institute in publishing the 100 most‐cited articles and also article type, study design, level of evidence, and the most important subjects among the 100 most‐cited papers. Results: In these 33 articles, the topics of 3300 most‐cited articles were introduced, as well as the introduction of the core journals, countries, and institutes in publishing top‐cited articles. The most common research topics in the field of dentistry cover a range of dental public health and pediatric dentistry to adhesive restorative dentistry and implantology. Dental materials, oral medicine, and pathology seem like inseparable topics of common research in dentistry. J Dent Res, which was mentioned in nine articles, was introduced as the journal with the publication of articles of highest citation. J Clin Periodontol and Oral Surgery, Oral Medicine, Oral Pathology, and Oral Radiology were in the second place, being mentioned in five articles. The USA, and two institutions the University of Texas, and the University of Michigan are orderly core country and institute for the production of most‐cited articles. Conclusion: Researchers and specialists can get familiar with the most productive author, journals, countries, and different institutes for publishing high‐quality articles in the field of oral and dental subjects by the means of the results of this article. Furthermore, the results of this study ranked the most cited article topics, which are of interest for publication, demonstrating the future map road oral and dental research.